How to run successful projects in Web time - O'Connell, Fergus (Artech House, 2001)
No matter what high-tech field you work in, but particularly in software development, shortening project time is of vital importance in gaining a competitive advantage. Here's the how-to book that describes a radical technique for doing just that. Taking an approach adopted from the motion picture industry, this innovative resource teaches you how to utilize techniques, such as "strip boarding" that greatly reduce project time and cost.